Pemodelan Dan Simulasi Cara Kerja Turbofan - Nurcahyani Dewi Retnowati; Dwi Nugraheny; Heri Sunaryo (Akademi Angkatan Udara, 2021)
Modelling and simulation how the gas turbine works on a turbofan uses several processes,namely making modeling using Blender software and making animation simulations using Unity software. The method used is Multimedia Development Life Cycle (MDLC). In the turbofan, it can be seen that there is a change in air temperature pressure which is indicated by a change in color, sound and engine rotation. This simulation uses an ideal cycle of thrust force of 1 to 6 rpm, according to the state of the engine on the ground which is not affected by altitude, velocity and speed of sound. Based on the results of the functionality test, it is known that all the functions and buttons in the simulation can run well according to their functions and can be run on Windows 7, Windows 8, and Windows 10 operating systems.